Studi Evaluasi Pengelolaan Biaya Pendidikan SMA Negeri 2 Mengwi - Nyoman Rara Widayani Astra; Kadek Rihendra Dantes; I Wayan Widiana (Jurnal Administrasi Pendidikan Indonesia, 2023)
This study aims to evaluate the implementation of education cost management at SMA Negeri 2 Mengwi for the 2021 academic year. The research design chosen in this study is an evaluative research design using the CIPP model (Context, Input, Process, Product). The population in this research is students, teaching staff and other educational staff at SMA Negeri 2 Mengwi in 2022, totaling 120 people. While the sample used in this study were 92 people. Context, input, process, product data in this study were collected using a questionnaire using a Likert scale of 1-5. The data analysis method used in this study is a quantitative descriptive analysis method. To determine the effectiveness of implementing the management of educational costs at SMA Negeri 2 Mengwi for the 2021 academic year, the raw scores were transformed into Z-scores, then into T-scores, then verified into the Glickman Quadrant prototype. Based on the research that has been done, the results show that: 1) the effectiveness of managing the costs of education in SMA Negeri 2 Mengwi in terms of the context, the results are effective (+), 2) the effectiveness of managing the costs of education in SMA Negeri 2 Mengwi, in terms of the input, the results are effective (+ ), 3) the effectiveness of managing educational costs for SMA Negeri 2 Mengwi in terms of the process obtained effective results (+), 4) the effectiveness of managing educational costs for SMA Negeri 2 Mengwi in terms of product obtained effective results (+), 5) the results of joint evaluation -the same with respect to the management of educational costs for SMA Negeri 2 Mengwi in terms of context, input, process, product, very effective results (+ + + +).